Evaluation of variations in the response of hypertensive patients in the outpatient installation of the UPT Puskesmas, Babat Lamongan District - Primanitha Ria Utami; Riana Prastiwi Handayani; Sheila Sheila (Universitas Muhammadiyah Malang, 2020)
Hypertension has long been a health problem that can have severe impacts on society. Measurement of blood pressure is one of the determinants of antihypertensive treatment's success, which can be seen from the reduction in the patient's blood pressure towards achieving the target blood pressure. Less than optimal blood pressure control is the most common risk factor for CVD and cerebrovascular disease. The role of the selection of antihypertensive therapy in each patient's condition is individual. Each patient will vary in response to various types of antihypertensive treatment. The research design carried out was retrospective descriptive with the observation of variations in answer to the use of antihypertensives in outpatient hypertension patients at the Babat Health Center with an examination period from January to December 2019. The study was divided into two groups, namely the positive and negative response groups. Patient characteristics data (age, sex, and treatment regimen) were statistically tested with the chi-square test to see whether there was a difference in eating or not between the two groups. It is said a positive response if the patient's blood pressure has decreased after three months of using antihypertensives. Harmful if after three months of antihypertensive use, there is no change in blood pressure or increased blood pressure. The evaluation was carried out on patients with negative responses, what factors were the causes. The results of patient characteristics, p> 0.05, were not significant differences between the two groups. There are variations in the negative response caused by the therapy regimen that is not optimal, lifestyle, and metabolism of antihypertensive drugs that are different for each individual.